Dutch Sources on South Asia c. 1600-1825 (Volume 3) : Archival Guide to Repositories Outside The Netherlands - Bes, Lennart (Brill | Manohar Publishers & Distributors, 2015)
This third volume in the series of Dutch Sources on South Asia c. 1600-1825 is a guide to Dutch archival materials and two-dimensional works of art kept in repositories outside the Netherlands. It contains detailed descriptions of the voluminous archives and collections deriving from the Dutch East India Company (VOC) stored in Chennai, Colombo, Jakarta, Cape Town, London and Paris, as well as miscellaneous Dutch sources scattered elsewhere in South Asia, Europe, North America and the Far East. Together with Volumes 1 and 2, which deal with the National Archives of the Netherlands and other repositories in the Netherlands respectively, it covers all known Dutch sources worldwide relating to more than two centuries of intensive Dutch contacts with the Indian subcontinent and Sri Lanka.